Some remarks on smooth renormings of Banach spaces - Hájek, Petr; Russo, Tommaso (Journal of mathematical analysis and applications, 2017)
We prove that in every separable Banach space X with a Schauder basis and a Ck-smooth norm it is possible to approximate, uniformly on bounded sets, every equivalent norm with a Ck-smooth one in a way that the approximation is improving as fast as we wish on the elements depending only on the tail of the Schauder basis. Our result solves a problem from the recent monograph of Guirao, Montesinos and Zizler.